Elimination of Image Saturation Effects on Multifractal Statistics Using the 2D WTMM Method - Juybari, Jeremy; Khalil, Andre (Frontiers in Physiology, 2022)
Imaging artifacts such as image saturation can restrict the computational analysis of medical images. Multifractal analyses are typically restricted to self-affine, everywhere singular, surfaces. Image saturation regions in these rough surfaces rob them of these core properties, and their exclusion decreases the statistical power of clinical analyses. By adapting the powerful 2D Wavelet Transform Modulus Maxima (WTMM) multifractal method, we developed a strategy where the image can be partitioned according to its localized response to saturated regions. \added{By eliminating the contribution from those saturated regions to the partition function calculations, we show that the estimation of the multifractal statistics can be correctly calculated even with image saturation levels up to 20%(where 20% is the number of saturated pixels over the total number of pixels in the image)}.